POPULATIONS GENETICS IN THE AMERICAN TROPICS XXVII. EXTINCTION AND RECOLONIZATION OF DEMES Vs. GENETIC VARIABILITY IN DROSOPHILA PSEUDOOBSCURA FROM COLOMBIA - Rodríguez , J.; Hoenigsberg , H. F. (Revista de la Academia Colombiana de Ciencias Exactas, Físicas y Naturales, 1987)
No-disponible